Influence of butyl group of tin chloride initiators on the non-isothermal DSC ring-opening polymerization of ε-caprolactone: The studies of kinetics, mechanism and polymer synthesis - Wanich Limwanich (2020)
© 2019 Elsevier B.V. The kinetics of ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) initiated by tin(II) chloride (SnCl2), dibutyltin(IV) dichloride (Bu2SnCl2) and tributyltin(IV) chloride (Bu3SnCl) was successfully investigated by non-isothermal DSC technique. The steric effect of butyl group of these tin chloride initiators on the catalytic performance of the ROP of ε-CL was studied by isoconversional kinetics methods. From isoconversional kinetics analysis by both Friedman and Kissinger-Akahira-Sunose (KAS) methods, the activation energy (Ea) values for the ROP of ε-CL initiated by SnCl2 were lower than Bu2SnCl2 and Bu3SnCl, respectively. The average values of frequency factor (A) for the ROP of ε-CL with SnCl2, Bu2SnCl2 and Bu3SnCl are 2.05 × 104, 1.34 × 108 and 2.64 × 108 min-1, respectively. The kinetics results clearly demonstrated that the reactivity of SnCl2 > Bu2SnCl2 > Bu3SnCl in the ROP of ε-CL. The effectiveness of all tin chloride initiators in the synthesis of poly(ε-caprolactone) (PCL) was investigated via bulk polymerization. The highly reactive SnCl2 produced high number average molecular weight PCL (M¯n = 3.5 × 104 – 1.1 × 105) in a short polymerization time. The increasing of butyl group in tin chloride initiators reduced the effectiveness in the synthesis of high molecular weight PCL. Furthermore, the mechanism of the ROP of ε-CL with tin chloride initiators was also studied and proposed through the coordination-insertion mechanism.